Delineating the Underground Water Quality for Irrigation and its Influences on the Soil Properties of Bali and Desuri tehsils of Pali district, Rajasthan - Chintu Chanwla; Ranjeet Singh; Ranveer Kumar Yadav; A.S. Godara; M.J. Kaledhonker; B.L. Meena (Annals of Agricultural Research, 2023)
In general, good quality irrigation water does not affect adversely the soil properties, however; the poor quality irrigation water is an important factor in the development of salinity and alkalinity in soils. Hence, a well-planned study of irrigation water and soils are needed to tackle soil and water problems. All information pertaining to this aspect is not yet available of this tract. Therefore, an urgent need is felt for extensive and well planned study both in the field and laboratory for suggesting suitable management practices for better utilization of underground water for irrigation and soils of this tract. Seventy-four geo referenced samples each of water and soil (0-15 cm depth) were collected from fifty two villages of Bali and Desuri tehsils of Pali district, Rajasthan during December 2020 from the tube wells/open wells which were used for irrigating the fields. The underground water for irrigation was found good, marginally saline, saline, high SAR saline and marginally alkali and soils were normal to alkaline in reaction with no salinity problem. The three management units were identified for better utilization of underground water for irrigation and soils of the study area for sustainable resource management.